Advances in the role of NK cells in MDS immune dysfunction and antitumor research - Wang, Yinglong; Feng, Zuxi; Li, Lijuan; Zhang, Liansheng (Frontiers in Immunology, 2025)
MDS is a heterogeneous group of myeloid neoplasms originating from hematopoietic stem cells, with a high risk of transformation into acute myeloid leukemia (AML). Natural Killer (NK) cells, crucial for their role in immune surveillance and efficient tumor cell lysis, experience functional impairments due to the complex microenvironment and cytokine dynamics in MDS. This article focuses on the mechanisms of NK cell dysfunction in MDS and the latest strategies to enhance NK cell activity to restore their anti-MDS efficacy, highlighting their key role and potential in MDS therapy.